2010
DOI: 10.5713/ajas.2011.10110
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Functional Characterization of Bovine Stromal Vascular Cells from Omental, Subcutaneous and Intramuscular Adipose Depots

Abstract: Anatomically separate fat depots differ in size, function, and contribution to pathological states such as the metabolic syndrome. We isolated pre-adipocytes from different adipose depots, omental, subcutaneous and intramuscular, of beef cattle, and cultured in vitro to determine the basis for the variations and attribute these variations to the inherent properties of adipocyte progenitors. The proliferating cells from all depots before the confluence were harvested and the proteome was analyzed by a functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The cellular development associated with adipose tissue growth involves both cellular hypertrophy (increase in size) and hyperplasia (increase in number). Rajesh et al (2010) reported that HSPB1 interact with insulin-like growth factor receptor 1 and its signal transducer, the serine/threonine kinase Akt, which together modulate an adipocyte metabolism. Specifically, the previous results suggested that HSPB1 was negatively correlated with an adipose metabolism (Kim et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The cellular development associated with adipose tissue growth involves both cellular hypertrophy (increase in size) and hyperplasia (increase in number). Rajesh et al (2010) reported that HSPB1 interact with insulin-like growth factor receptor 1 and its signal transducer, the serine/threonine kinase Akt, which together modulate an adipocyte metabolism. Specifically, the previous results suggested that HSPB1 was negatively correlated with an adipose metabolism (Kim et al, 2011).…”
Section: Resultsmentioning
confidence: 99%